Optimizing Student Engagement in Social Studies Through the Team Quiz Approach - Hilman, Hilman; Sulhan Hadi, Muh.; Eka Saputra, Bambang; Suhupawati, Suhupawati; Murcahyanto, Hary (IJE : Interdisciplinary Journal of Education, 2025)
This study aims to enhance students' learning outcomes and engagement in Social Studies through the implementation of the Team Quiz (TQ) method in the topic of New Order Government. The research method employed is Classroom Action Research (CAR), conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observations, learning outcome tests, and reflections on the learning process. The findings indicate that the implementation of Team Quiz positively impacts students' participation and comprehension. In Cycle I, the students' mastery level reached 61% with an average score of 74, while in Cycle II, it increased to 91% with an average score of 85. This improvement is attributed to greater student participation in group discussions, more active interaction, and the competitive nature of the quiz, which enhanced learning motivation. Additionally, this model created a more dynamic and engaging learning environment. Despite its effectiveness, several challenges were encountered, such as the dominance of higher-achieving students in group discussions and limited discussion time. Therefore, teachers need to ensure an equitable distribution of roles within groups and provide more intensive guidance. Based on the study's findings, the Team Quiz method is recommended as an innovative teaching strategy to enhance student engagement and learning outcomes. Furthermore, it can be adapted to other subjects to foster a more interactive and effective learning environment.